Peran Humas Sekolah Dalam Meningkatkan Kepercayaan Publik Melalui Media Sosial (Studi Lembaga Pendidikan Islam) - Umi Ayu Syufiawati; Ummi Kulsum; Sulis Maryati (CV. ITTC INDONESIA, 2026)
School public relations plays a strategic role in building institutional image and public trust, particularly in the digital era, which demands transparency, speed, and accuracy in the dissemination of information. This article aims to analyze the role of school public relations, the use of social media as a communication strategy, and the implementation of public relations practices in enhancing public trust in Islamic educational institutions. This study employs a qualitative approach using the library research method. Data were obtained from relevant scientific journal articles discussing educational public relations, social media, institutional image, and public trust. The data were then analyzed through the stages of data collection, reduction, thematic classification, comparison, and conclusion drawing. The findings indicate that social media can expand the reach of information, strengthen two-way communication, increase public engagement, and support the development of a positive institutional image when managed in a planned, consistent, accurate, and ethical manner. Effective implementation requires institutional policies, a clear division of responsibilities within the public relations team, public mapping, content calendars, information verification, responsive services, issue management, data protection, and periodic evaluation. In Islamic educational institutions, such management should be grounded in the values of honesty, trustworthiness, transparency, responsibility, and courtesy. Therefore, public trust is established through consistency between the information conveyed through social media and the quality of services and real experiences received by the public from the institution.